Chestiunea familiei în RSSM în contextul Perestroikăi, 1985-1988 / The question of family policy in the Moldavian SSR in the context of Perestroika (1985-1988) - Diana Caşu (Tyragetia, 2015)
The Perestroika that has been launched by Mikhail Gorbachev in mid-1985 was a very ambitious program of further modernization of the Soviet Union aimed at solving the many problems of Soviet society. Among these problems was the policy on family. In this regard, the 27th Congress of CPSU (February-March 1986) adopted a number of measures that were designed to change the family policy. The Government of the Moldavian SSR and the Central Committee of the CPM took the lead in implementing this program. The responsibilities were distributed among the various ministries, agencies, cultural and social organizations. There were organized several public opinion polls to obtain information about the life of families in Soviet Moldavia. As a result, there was revealed a very diﬃcult situation: criminality among teenagers, alcoholism in families, growing tendency of divorces, hygienic diﬃculties and so on. These problems were inherited by post-communist societies in the countries of the former Soviet Union, including the Republic of Moldova.